The Adapting of an Enterprise Organizational Management Structure to Alterations - Vilhutska, Roksolana (Видавництво Львівської політехніки, 2013)
The ways of Enterprise Organizational Management Structure (EOMS) adapting to alterations in inner and outer environment have been described in the abstract. The process under consideration takes place in the way of combining of new structural sections to the ones already existing.Under the example of EOMS we described the process of plurality combination, which is based on the axiom of their inclusion and intersection.
Keywords: organizational structure of management; restructuring; axiom of inclusion; inner and outer environment; plurality of elements; theory of pluralities